Didattica Speciale per le Disabilità Comunicative: il Potere della Comunicazione secondo Janice Light - Saverio Fontani (Firenze University Press, 2017)
The Augmentative and Alternative Communication (AAC) is an assistive technology which can compensate the communication deficits associated with various developmental disabilities. In this paper the theoretical background of the approach is presented, with emphasis on the prototypical contributions of J. Light, and the opportunities for the Special Education of students with complex communicative needs are discussed.